Condições de saúde bucal e utilização de serviços odontológicos por pessoas que vivem com HIV/AIDS no município de Fortaleza-Ceará - Araújo, Denis Bezerra de (2010)
Knowledge about the oral health status and the use of dental services for people living with HIV / AIDS (PLWHA) is a factor important to plan actions in order to provide a focus Quality dental care to this population. This study aimed to identify the main factors related to utilization of dental services and oral health status of PLWHA in Fortaleza - Ceará. To this end, A transversal study with a quantitative approach, developed August to December 2009 with PLWHA who were accompanying us infectious disease clinics of a university hospital (HUWC) and Medical Specialties Center José de Alencar (CEMJA). We collected Data on the clinical and laboratory such persons, on conditions sociodemographic, utilization of dental services and the conditions of oral health of this population. The study included 173 patients; 72.3% male and 27.7% female, with a mean age of 36.4 years. Of these, 50.9% (88/173) said they had not yet consulted with a dentist after HIV infection and 52.6% (91/173) of participants said not disclose their HIV status to the dentist before a treatment dentistry. The study also showed that searching for dental care public services (PR: 2.39, 95% CI 1.23 to 4.16, p <0.001) and reveal the condition serology for the dentist (PR: 2.11, 95% CI: 1.03 - 4.31, p <0.001) were significantly associated with having difficulty in accessing these services. There was a high prevalence (61.3%), periodontal disease (87.3%) and changes in oral mucosa (12.7%) in this population. It was evident that there is no statistically significant association between caries and immunological conditions of seropositive patients (p> 0.05). However, the presence of changes in oral mucosa was associated statistically significant with low CD4 count (PR: 4.20; 95% CI: 1.74 to 10.13, p <0.001) and high levels of plasma viral load (PR: 4.74; 95% CI: 2.11 to 10.67, p <0.001). This study concluded that there is at investigated population a high prevalence of oral diseases, showing therefore, great need for dental treatment. However, also observed that there are limitations on access to these people oral health services.